Hydrology and water resourses symposium 1985, Sydney, 14-16 May 1985 : preprints of papers - Institution of Engineers (Australia) National Committee on Hydrology and Water Resources; Hydrology and Water Resources Symposium (1985 : Sydney) ([s l] : [s n])
07